Factors affecting acceptance of “Bring Your Own Device” (BYOD) policy at HeiTech Padu Berhad / Najuwa Aqilah Mohd Muslim - Mohd Muslim, Najuwa Aqilah (Faculty of Business and Management, 2018)
This research involves discovering the role of perceived values in acceptance of BYOD policy. The purpose of this research is to find out the level of acceptance about BYOD policy among HeiTech Padu Berhad employees. This survey research is conducted by distributing questionnaires to workers in 21 departments inside HeiTech Padu Berhad that include Finance, Legal, Human Resources, Safety and Health, Marketing, Sales and Services, Project Monitoring and Compliance, Audit Assurance and others. The total number of staff in HeiTech Padu Berhad at HeiTech Village is 260 staff. The sample sizes taken are only 155 respondents. This research is to determine whether the three variables which are benefits, sacrifices and behavioral intention have a significant impact on acceptance of BYOD at HeiTech Padu Berhad. The result indicates that benefits, sacrifices and behavioral intention are related to acceptance of BYOD policy at HeiTech Padu.